Pertumbuhan dan Hasil Berbagai Varietas Kacang Hijau (Vigna radiata (L.) Wilczek) pada Kadar Air yang Berbeda - YUDHANI WIDHYA HARTIWI; GEDE WIJANA; RINDANG DWIYANI (Fakultas Pertanian Universitas Udayana, 2017)
Growth and Yield of Various Mung Bean Varieties (Vigna radiata (L.) Wickzek in Different Water Content. Mung bean (Vigna radiata (L.) Wilczek) is a commodity crop beans are commonly grown on dryland and high protein. Problems encountered in cultivation of mung bean in dry land is low results, one of them the limited seed of drought stress tolerant therefore needs to be done against drought stress research production of mung beans. Objective to know the growth and the results of various varieties of mung beans at different water levels. This experiment using Random Design complete with two factors. The treatment consists of the water content of the soil with a capacity of 100% airy, 75%, 50%, 25% and varieties of Fore Belu, Kutilang, Vima-1, and Sriti. The results of the experiment demonstrated the interaction between moisture content and varieties against the number of pods per plant, number of seeds per plant dry weight, dry seeds per plant, seeds of oven dry weight per plant dry weight and the oven 100 seeds. Moisture content of the soil with a roomy capacity (100%) gives the results of dry weight per plant seeds under the highest (17.2 g) compared to other treatments. Varieties that produce the highest growth found in the varieties of Sriti. Moisture content of the soil with a capacity of 100% airy gives the best results on the plant mung beans. Most varieties are tolerant of most soil water content lower than the capacity of the airy is Sriti varieties.